Risk and Economic Burden of Peristomal Skin Complications Following Ostomy Surgery - Taneja, Charu; Netsch, Debra; Rolstad, Bonnie Sue; Inglese, Gary; Eaves, Deanna; Oster, Gerry (Journal of wound, ostomy, and continence nursing, 2019)
The purpose of this study was to examine the incidence and economic burden of peristomal skin complications (PSCs) following ostomy surgery. Retrospective cohort study based on electronic health records and administrative data stores at a large US integrated healthcare system. The sample comprised 168 patients who underwent colostomy (ICD-9-CM 46.1X) (n = 108), ileostomy (46.2X) (n = 40), cutaneous ureteroileostomy (56.5X), or other external urinary diversion (56.6X) (n = 20) between January 1, 2012, and December 31, 2014. The study setting was an integrated health services organization that serves more than 2 million persons in the northeastern United States. We scanned electronic health records of all study subjects to identify those with evidence of PSCs within 90 days of ostomy surgery and then examined healthcare utilization and costs over 120 days, beginning with date of surgery, among patients with and without evidence of PSCs. Testing for differences in continuous measures between the 3 ostomy groups was based on one-way analysis of variance; testing for differences in such measures between the PSC and non-PSC groups was based on a t statistic, and the χ statistic was used to test for differences in categorical measures. Sixty-one subjects (36.3%) had evidence of PSCs within 90 days of ostomy surgery (ileostomy, 47.5%; colostomy, 36.1%; urinary diversion, 15.0%; P < .05 for differences between groups). Among patients with evidence of PSCs, the mean (SD) time from surgery to first notation of this complication was 26.4 (19.0) days; it was 24.1 (13.2) days for ileostomy, 27.2 (21.1) days for colostomy, and 31.7 (25.7) days for urinary diversion (P = .752). Patients with PSCs were more likely to be readmitted to hospital by day 120 (55.7% vs 35.5% for those without PSCs; P = .011). The mean length of stay for patients readmitted to hospital was 11.0 days for those with PSCs and 6.8 days for those without PSCs (P = .111). The mean total healthcare cost over 120 days was $58,329 for patients with evidence of PSCs and $50,298 for those without evidence of PSCs (P = .251). Approximately one-third of ostomy patients developed PSCs within 90 days of their surgery. Peristomal skin complications are associated with a greater likelihood of hospital readmission. Our findings corroborate results of earlier studies.